The tadpole of Elachistocleis cesarii Miranda-Ribeiro, 1920 (Anura, Microhylidae) - de Medeiros Magalhães, Felipe; Santana, Diego José; Neto, Antonio Mollo; Garda, Adrian Antonio (Zootaxa, 2012)
The genus Elachistocleis Parker currently comprises 13 species widely distributed from Panama to central Argentina, east of the Andes (Caramaschi 2010). Because most species are difficult to diagnose and several currently recognized species might represent more than one lineage, tadpoles can contribute to the resolution of taxonomic problems (Rossa-Feres & Nomura 2006).